THE EFFECT OF WORK STRESS AND WORKLOAD ON ORGANIZATIONAL COMMITMENT - Kurniadin, Adin (Universitas Kuningan, 2023)
The aim of the study was to analyze the influence of job stress and workload on employees' organizational commitment, both collectively and individually. The research adopted a descriptive-verification method with a quantitative approach. The study used a saturated sample of 32 employees from Bawang Goreng Harum Berkah Company, which constituted the total populations. Data collection was done through a valid and reliable questionnaire. The data analysis techniques included descriptive analysis, classical assumption tests, multiple regression analysis, coefficient determination tests, and hypothesis testing. The research results indicated that 1) Job stress and workload collectively had a significant influence on organizational commitment. 2) Job stress had a negative and significant effect on organizational commitment individually. 3) Workload had a negative and significant effect on organizational commitment individually. Overall, the findings revealed an inverse relationship, suggesting that reducing job stress and workload could enhance organizational commitment. Adjusting working hours and providing clear instructions regarding task execution could be potential solutions to address the high job demands and confusion experienced by employees, leading to an increase in organizational commitment.